Modeling and optimization of refinery hydrogen management system considering hydroprocessing mechanisms and constraints - Zhou, Yingqian; Yang, Minbo; Wang, Yufei (Chemical engineering science, 2026)
•The coupling sink-source model expresses hydroprocessing mechanisms.•The coupling sink-source model expands optimization dimension for HNS.•The interactions between HNS and hydroprocessing unit operations are revealed.•The linear representation-based optimization framework achieves global optimization. Hydrogen network synthesis (HNS) in refineries serves as an effective approach to enhance hydrogen utilization efficiency, optimize network topology, and reduce operating costs. Conventional methods typically rely on the fixed hydrogen source and sink parameters, which deviates from the refinery reality. To address this problem, this work develops a data-driven optimization framework that hybrids rigorous simulation and machine learning to establish a coupling hydrogen sink-source model with hydroprocessing mechanisms and product specifications. The proposed framework comprehensively incorporates reaction-separation-compression systems in HNS. A mixed-integer nonlinear programming model is formulated for optimal synthesis of hydrogen networks. The results of systematic case studies reveal that implementing the coupling sink-source model expands the optimization dimensions, thereby reducing the pure hydrogen consumption in hydroprocessing units and decreasing the total annualized cost (TAC) by 9.35 %∼10.00 %. The consideration of compressor sharing contributes to a slight TAC reduction due to its low-cost proportion, but it enables additional cost savings through topology reconfiguration. The synergistic optimization of hydrogen networks and hydroprocessing units is achieved in this work.